Use of Tracker Application on Kinetic Orbital Art (KOA) and Magic Gyroscope as Physics Learning Media - Desi Ramadhanti; Heru Kuswanto; Hestiana Hestiana; Sabila Yasaroh; Aisha Azalia (Postgraduate, University of Mataram, 2021)
This article aims to explain the use of tracker applications on Kinetic Orbital Art (KOA) and magic gyroscope in physics learning. This study uses descriptive analysis methods. The accelerated value of earth's gravity in the kinetic circular motion of orbital art and magic gyroscopes aided analysis with tracker applications and Microsoft Excel programs. The results will be compared to get a graph of position relationships with time. From research conducted on the motion of KOA and magic gyroscope assisted tracker application obtained acceleration value is 9.44 m/s2 and 9.56 m/s2. The graph obtained from both objects is not referred to as parabolic motion on the KOA chart resembles a parabolic motion, while the motion of the magic gyroscope is referred to as circular motion. Thus, the use of tracker application on KOA and magic gyroscope can be recommended as a learning medium of Physics in schools